Ultrastrong light-matter coupling in electroluminescent organic microcavities. Issue 1 (November 2015) - Gambino, Salvatore; Genco, Armando; Accorsi, Gianluca; Di Stefano, Omar; Savasta, Salvatore; Patanè, Salvatore; Gigli, Giuseppe; Mazzeo, Marco
Graphical abstract: Effect of the ultrastrong coupling regime on the electrical and optical properties of microcavity-OLEDs. An electroluminescent emission linewidth of only 28 meV (around one order of magnitude narrower then that of the corresponding photoluminescence) has been achieved. Highlights: Study of EL from polariton OLEDs in the ultrastrong coupling regime. Effects of the ultrastrong coupling regime on microcavity-OLEDs. Enhancement of the coupling factor ( g ) from 31% up to 48%. Enhancement of the EL emission linewidth up to 28 meV. Abstract: In this work, we explore the effects of the ultrastrong coupling regime between light and molecular excitons on the electrical and optical properties of microcavity-OLEDs. We studied two different samples having a coupling value of 31% and 48%. The main effect of the ultrastrong interaction is on the electroluminescent emission linewidth which was only 28 meV, that is about 12-fold narrower than that of the corresponding photoluminescence of the uncoupled material and even half the linewidth of photonic (weak-coupled) microcavity working at the same wavelength.